2014
DOI: 10.1111/ases.12111
|View full text |Cite
|
Sign up to set email alerts
|

Role of the transumbilical laparoscopic‐assisted single‐channel, single‐port procedure in an interval appendectomy for pediatric mass‐forming appendicitis: A preliminary retrospective analysis

Abstract: The single-channel, single-port procedure was successfully performed in over 70% of the patients. This preliminary retrospective analysis indicates that the procedure is safe and potentially beneficial in children with mass-forming appendicitis who require laparoscopic interval appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…Although laparoscopic appendectomy has been shown to offer many advantages with regard to shorter hospital stay, less postoperative pain, and lower rate of infections, few studies have assessed the safety and effectiveness of SLIA for patients with complicated appendicitis . Ohno and Kang et al showed the safety and feasibility of SLIA without comparison with EA for appendicitis with a peri‐appendiceal abscess in pediatric and adult patients, respectively, and reported that the complication rate was 8.0%. The morbidity rate reported in other reports on IA for complicated appendicitis without single‐site laparoscopic appendectomy was 12.4%‐15%, which is similar to our morbidity rate .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although laparoscopic appendectomy has been shown to offer many advantages with regard to shorter hospital stay, less postoperative pain, and lower rate of infections, few studies have assessed the safety and effectiveness of SLIA for patients with complicated appendicitis . Ohno and Kang et al showed the safety and feasibility of SLIA without comparison with EA for appendicitis with a peri‐appendiceal abscess in pediatric and adult patients, respectively, and reported that the complication rate was 8.0%. The morbidity rate reported in other reports on IA for complicated appendicitis without single‐site laparoscopic appendectomy was 12.4%‐15%, which is similar to our morbidity rate .…”
Section: Discussionmentioning
confidence: 99%
“…Single‐site laparoscopic interval appendectomy (SLIA) after CT to ameliorate inflammation and eradicate the abscess may be safer and less invasive than EA, providing the advantages of minimally invasive surgery, such as reduced postoperative pain and improved cosmetic outcome, even if the appendicitis is severe. However, only a few studies of SLIA for complicated appendicitis have discussed its effectiveness . Therefore, the present study investigated patients with severe complicated appendicitis who underwent SLIA and analyzed perioperative outcomes compared to EA.…”
Section: Introductionmentioning
confidence: 99%
“…Bu farklı yaklaşımlar içerisinde yer alan ve en sık kullanılan yöntem olan elektif şartlardaki İA için literatürde pek çok farklı çalışma bulunmaktadır (4)(5)(6)9,10,14) .…”
Section: Discussionunclassified
“…Yara yeri akıntısı ve enfeksiyon, hematom oluşumu, ameliyat sonrası uzamış ileus ve ince bağırsak tıkanıklıkları literatürde en sık bildirilmiş olan komplikasyonlardır (19,20) . İşlemin laparoskopik olarak yapılması komplikasyon oranını, hastanede kalış süresini daha da azaltmaktadır (6) . Bu çalışmada 36 hastanın yalnızca ikisinde (%5,5) ameliyat sonrası komplikasyon geliştiği gözlenmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation